An alternative thermal approach to evaluate the wettability of solder alloys - Santos, Washington L.R.; Silva, Bismarck L.; Bertelli, Felipe; Spinelli, José E.; Cheung, Noé; Garcia, Amauri (Applied thermal engineering, 2016)
[Display omitted] •A thermal approach is proposed to qualitatively evaluate the wettability of solders.•The approach is based on experimental results of solder/substrate thermal conductance.•High temperature Zn-Sn solders are experimentally investigated.•The approach is validated against experimental contact angles of wetting tests.•The results indicate increase in wettability with decrease in alloy Sn content. The aim of the work is to propose an alternative method to qualitatively evaluate the wettability of different alloys of a particular alloy system. The technique is based on a thermal approach supported by experimental/theoretical methodologies involving a directional solidification procedure and numerical simulations based on the solution of the inverse heat conduction problem (IHCP). The wettability strongly affects the heat ability to flow across the alloy/substrate interface during solidification, which is construed as a heat transfer coefficient (hg). Particularly, for the alloys used in soldering processes, the wettability plays an important role in the integrity of solder junctions, being a fundamental parameter for selecting the most appropriate solder composition. The experiments were carried out with high temperature Zn-Sn solder alloys (10, 20, 30 and 40wt%Sn) in a solidification device in which heat is extracted only through a water-cooled steel bottom. Experimental thermal profiles collected during solidification are used as input data to solve the IHCP and determine expressions hg vs. time for each alloy examined, permitting a tendency of wettability to be established. In order to validate the wetting behavior indicated by the hg values, alloy/substrate contact angles (θ) were measured on a steel substrate using a goniometer. It is shown that both hg and θ indicate improvements in wettability with the decrease in the alloy Sn content.